A Historical and Critical Assessment of Parametricism as an Architectural Style in the 21st Century - Youns, Ameen Mokhles; Grchev, Kokan (Mdpi, 2024)
Architectural styles have evolved, with distinct periods marked by unique styles that reflect broader artistic movements. Despite extensive research on traditional and contemporary architectural styles, there remains a gap in understanding the distinctiveness and contributions of Parametricism as a 21st-century architectural style. This study aims to critically examine the emergence and development of Parametricism, aiming to highlight whether it represents a fundamental evolution in architectural thought and practice or primarily a methodological innovation. Through a comprehensive investigation of its formal characteristics, historical roots, and relationships with other architectural movements, this study seeks to discuss Parametricism's unique contributions to modern architecture. This research is crucial as it addresses the underexplored area of parametric design's impact on architectural theory and practice, offering a critical analysis that situates Parametricism within the broader context of 21st-century architectural styles. By clarifying the definition and position of Parametricism, this study aims to enrich both the state of the art and the state of practice in the field, providing valuable insights for scholars, practitioners, and students of architecture. Through this critical assessment, the paper contributes to the ongoing discourse on the evolution of architectural styles, highlighting the originality and significance of Parametricism in contemporary architecture.
Keywords: architecture style; style; parametricism; 21st century; parametric design